Changes to Hearing Levels Over the First Year After Stapes Surgery: An Analysis of 139 Patients. Issue 7 (August 2018) - Nash, Robert; Patel, Bhavesh; Lavy, Jeremy
Abstract : Background: Stapes surgery is performed for hearing restoration in patients with otosclerosis. Results from stapes surgery are good, although a small proportion will have a persistent conductive hearing loss and will consider revision surgery. The timing of such surgery depends on expected changes to hearing thresholds during the postoperative period. Methods: We performed a retrospective case series analysis of a database of outcomes from stapes surgery performed between July 26, 2013 and March 11, 2016 at one center. Hearing outcomes over the year subsequent to surgery were recorded. Results: There was a significant improvement in hearing outcomes between the postoperative visit at 6 weeks (mean air-bone gap 6.0 dB) and the hearing outcome at 6 months (mean air-bone gap 3.3 dB) ( p  < 0.01). This improvement was maintained at 12 months (mean air-bone gap 3.1 dB), although there were individual patients whose hearing outcome improved or deteriorated during this period. Improvements in air conduction thresholds mirrored improvements in air-bone gap measurements. Conclusion: Patients with an initial suboptimal or poor result after stapes surgery may observed improvement in their hearing thresholds in the year after surgery. These patients may have large preoperative air-bone gaps, and have a trend to have obliterated footplates. Revision surgery should not be considered until at least 6 months after primary surgery.